Electric-field manipulation of magnetization in an insulating dilute ferromagnet through piezoelectromagnetic coupling - Dariusz Sztenkiel; Katarzyna Gas; Nevill Gonzalez Szwacki; Marek Foltyn; Cezary Śliwa; Tomasz Wojciechowski; Jarosław Z. Domagala; Detlef Hommel; Maciej Sawicki; Tomasz Dietl (Communications Materials)
Abstract The electric field control of magnetization is of significant interest in materials science due to potential applications in many devices such as sensors, actuators, and magnetic memories. Here, we report magnetization changes generated by an electric field in ferromagnetic Ga1−x Mn x N grown by molecular beam epitaxy. Two classes of phenomena have been revealed. First, over a wide range of magnetic fields, the magnetoelectric signal is odd in the electric field and reversible. Employing a macroscopic spin model and atomistic Landau-Lifshitz-Gilbert theory with Langevin dynamics, we demonstrate that the magnetoelectric response results from the inverse piezoelectric effect that changes the trigonal single-ion magnetocrystalline anisotropy. Second, in the metastable regime of ferromagnetic hystereses, the magnetoelectric effect becomes non-linear and irreversible in response to a time-dependent electric field, which can reorient the magnetization direction. Interestingly, our observations are similar to those reported for another dilute ferromagnetic semiconductor Cr x (Bi1−y Sb y )1−x Te3, in which magnetization was monitored as a function of the gate electric field. Those results constitute experimental support for theories describing the effects of time-dependent perturbation upon glasses far from thermal equilibrium in terms of an enhanced effective temperature.